2001
DOI: 10.1093/milmed/166.12.1091
|View full text |Cite
|
Sign up to set email alerts
|

Diverting Loop Colostomy for the Treatment of Refractory Gastrointestinal Bleeding Secondary to Radiation Proctitis

Abstract: Chronic radiation proctitis is an uncommon and serious complication of radiotherapy for pelvic malignancies. It has been suggested that fecal stream diversion decreases bowel irritation, resulting in decreased rectal bleeding. We report on the outcome of patients after a diverting loop colostomy for the treatment of severe radiation proctitis. All consecutive patients with chronic proctitis treated with diverting loop colostomy for bleeding at one institution between October 1991 and June 1999 were studied. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 0 publications
0
13
0
1
Order By: Relevance
“…An ostomy can also improve symptoms related to incontinence and stricture, but it has a limited effect on bleeding. At least one study [67] showed significant improvement in bleeding from a diverting loop colostomy but not complete resolution. Diversion will improve symptoms but without additional interventions, the improvements in symptoms are unlikely to persist after an ostomy reversal.…”
Section: Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…An ostomy can also improve symptoms related to incontinence and stricture, but it has a limited effect on bleeding. At least one study [67] showed significant improvement in bleeding from a diverting loop colostomy but not complete resolution. Diversion will improve symptoms but without additional interventions, the improvements in symptoms are unlikely to persist after an ostomy reversal.…”
Section: Treatmentsmentioning
confidence: 99%
“…Diverting loop colostomy was described in one study as a successful way of controlling bleeding [67], but in many instances, proctectomy may be the only option available. When strictures are an issue, a diversion of the stool stream will often result in a significant improvement of symptoms.…”
Section: Treatmentsmentioning
confidence: 99%
“…Colostomy has been used to treat haemorrhagic radiation proctitis [14]. Although diversion of the faecal stream reduces the bacterial load to the irradiated section of the bowel and decreases the bleeding, it carries the risk of surgical complications.…”
Section: Discussionmentioning
confidence: 99%
“…Faecal diversion with a colostomy or ileostomy rarely controls blood loss completely in those with severe and intractable symptoms [62], and bowel resection may therefore be considered [9]. It should be remembered that the microvascular damage caused by radiation not only causes the symptoms of radiation proctopathy, but also significantly impairs healing after surgery [63].…”
Section: Surgical Treatmentsmentioning
confidence: 99%